Analisis Faktor-Faktor yang Mempengaruhi Minat Penggunaan Fintech Sebagai Alat Pembayaran oleh UMKM di Kota Batam - Novison; Poniman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Technological advances in the financial sector can already be felt by entrepreneurs with innovations in the use of technology such as financial technology or abbreviated as fintech. Fintech is a service that aims to speed up various financial services such as transactions for MSMEs. They use fintech as a payment tool to simplify and speed up the payment process. This research aims to evaluate the influence of perceived ease of use, benefits of use, risks and trust on interest in using fintech as a means of payment. In the city of Batam, there are around 81,575 MSMEs registered with the Department of Cooperatives and Micro, Small and Medium Enterprises. The research sample was 100 MSMEs selected using the Slovin formula and simple random sampling method. The t test results show that perceived ease of use and perceived benefits of use significantly influence interest in using fintech as a means of payment. However, risk and trust do not have a significant influence on interest in using fintech as a means of payment. The results of the f test show that together, perceived ease of use, perceived benefits of use, risk and trust have an influence on interest in using fintech as a means of payment.